LEGAL SUPPORT OF CASHLESS PAYMENTS IN ECONOMIC ACTIVITY - Koлісник Aртем; Пилипишин , Станіслав; Авраменко, Олександр; Потапенко, Людмила (Socio-economic relations in the digital society, 2020)
The key areas of legal regulation of non-cash settlements in financial and economic activity are investigated. It was proved that calculations in financial and economic activity are certain relations which appear in connection with the fulfillment of monetary obligations arising from the law or the contract. As a result they are part of the monetary circulation that is regulated by the state purpose, ensuring the redistribution of financial resources of the state and control of their use. It was also established that the subject of regulation of the cashless settlement institution is not only the economic civil-legal relations that arise between customers and the bank, but also administrative-financial and information relations that are related to the circulation of documents in paper and electronic form. It was researched that during the execution of non-cash payments, documents are created by normative legal acts of the Ukrainian National Bank and in most cases there is an exchange of information between banks and cash flow systems which are kept on payers’ accounts. It was noted that the issue of calculation genesis as well as identification of the relationship between the legal regulation of primary forms and modern legal framework will give the opportunity to set specifics and identify features for the development of legal regulation of cashless settlements. In addition, it will help to determine the right ways for improvement the economic and legal regulation of non-cash payments in modern conditions. It is proved that in the conditions of active introduction of modern information and telecommunication technologies in the activity of financial institutions, the emergence of e-commerce, the emergence of new financial instruments and the spread of electronic banking systems, the development of the payment services market is characterized by increasing customer demand for non-cash payments. Therefore, the development of recommendations for improving the legal regulation of non-cash payments in economic activities should be based on a comprehensive analysis of the interests of both market participants and the state.